Utilisation du bois dans les pêcheries côtières du Cameroun - Hyacinthe Angoni; Alphonse Pouokam Tatchim; Bernard Aloys Nkonmeneck; Elie Nguekam (Revue d'ethnoécologie)
Kribi is situated in the Cameroon coastal zone, in the Southern Region and in the Ocean administrative department.The coastal border in the South Cameroon is characterized by a mangrove vegetation which is part of the Rio Ntem mangrove zone.Fishing activities constitutes the main income generating activity for the populations. For the conservation and the transformation of the fish, drying is widely practiced in the region. This technique consumes enormous quantities of wood causing severe threats on biodiversity.This study which extends from Kribi to Campo has as objective, to study the uses of wood and to identify the impacts of its exploitation in the environment.Inquiries with the fishermen communities, the actors of the fish drying activities in which the dryers and the salesmen of wood, the biometric measures were collected on harvested wood.It comes out of this study that there are two types of wood supply. The populations cut the wood directly from the forest because of the nearness of forests. Fish drying represents 60% of the various uses of the fire wood. In comparison with the classic drying method, the improved new drying system allows the reductions of the wood consumption in the level of 50%. Average consumption in traditional drying system is about 6,8 m3 against 3,4 m3 for the new improved drying method. The wood of mangrove is more or less used by the dryers. On the other hand, Sambi (Uapaca guineensis) is most appreciated species in the fish drying activity.